Effet du cuivre sur les paramètres morphologiques et la mobilité des éléments minéraux (sodium, potassium et calcium) chez la fève (Vicia faba. L). - MEDJAHED, Wahiba; TIUORIRI, Amina (My University, 2016)
Copper is an essential oligoelement for the plants nutrition, phototoxic at very high concentration. The contamination of soil by copper is present when anthropogenic inputs are important. It means that when its content is soil is higher at pedogeochemical bottom, it causes an increase of impacts risks to the environment. The phytotoxicity of copper is translated by a decrease of the total biomass of the plant and a disturbance of the mineral nutrition of the plants by the modification of the mineral elements concentration in the aerial and root parts. The aim of our work is to follow the behavior of the bean ( Vicia faba L) in front of the metallic stress induce by copper, by the evaluation of the effects procured by this stress on the morphological settings and on the mobility of the mineral elements Na+,K+ and Ca++ in different parts of the plant. The study was conducted on variety of bean, Sidi Aich; the germinated seeds have been planted in pots containing soils contaminated by different concentrations of copper sulfate. (0, 200, 400, 600, 800, 1000 ppm). The resultants show that the presence of copper at high concentrations causes a decrease of the morphological settings of bean and provokes modifications of the concentrations of Na+, K+ and Ca++ in the different organs of the bean. These observations have been particularly reported on plants submitted to a dose of 1000 ppm
Keywords: phytotoxicity; copper; morphology; mobility; Na+; K+; Ca++; Vicia faba L .; cuivre; phytotoxicité; paramètres morphologiques; concentration de Na, K et Ca